Labor analgesia related to obstetric outcomes (Research, Society and Development, 2021)
The issue of the use of analgesia in childbirth, even though it is not commonly adopted in Brazil, has been largely replaced in respect of how to make this moment less painful and with less unfavorable outcomes, both for the newborn and for the mother. Objective: This article aims to assess the relationship between the use of anesthetic techniques and the obstetric outcome of pregnant women during labor, based on articles published in the database. Methods: This is an integrative review that aims to analyze and synthesize that the literature brings about labor analgesia and its possible obstetric outcomes. The search for articles was carried out in the following databases: Scientific Eletronic Library Online (SciELO) and in Latin American and Caribbean Literature (LILACS); in addition to the PUBMED portal. Results and Discussion: Despite being satisfactory to control pain, the administration of local anesthetics can trigger several unfavorable effects. During a study, the length of the expulsive period of labor, an important fetal bradycardia, in addition to the increase in the number of instrumental deliveries, stood out among the studies. Final considerations: This article considers that there is a benefit of using analgesia for pain relief and comfort during childbirth, but it was observed that there is a relationship between its use and: assisted vaginal delivery, delay in the beginning of lactation, increase in the second stage of delivery and fetal bradycardia.